The Influence Of Brand Equity Dimensions Towards Purchase Intention Of Samsung Smartphone On College Student At The Faculty Of Economics And Business University Of Brawijaya Malang - Gusmarindra, Tendy (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The aim of this study is to examine the influence of Brand Equity (Brand Awareness, Brand Association, Perceived Quality and Brand Loyalty) on Purchase Intention of Samsung Smartphone on College Student in Faculty Economics and Business University of Brawijaya Malang. The research is explanatory research which explains the causal relation between the variables through hypothesis testing. The data collection technique of this study uses questionnaires. This study used 120 samples are the student who ever used Samsung Smartphone. The sampling technique used purposive sampling and the research instruments were tested using the Validity Test, Reliability Test, The hypothesis used Partial (t-Test) using Partial Linear Square (PLS) analysis technique to analyze the data. The result from this study showed that variable of brand awareness, brand association, perceived quality, and brand loyalty provides good value and each of them made a significant effect to purchase intention.Keywords:Brand Awareness, Brand Association, Perceived Quality, Brand Loyalty and Purchase Intention.